The design and manufacture of massively scalable inertial focusing prototype microfluidic devices - Thomas Carvell; Paul Burgoyne; Alasdair R. Fraser; Helen Bridle (PLoS ONE, 2025)
Microfluidics is a rapidly expanding field and microfluidic devices have been used in a variety of biomedical applications such as cell sorting, disease diagnostics and various lab-on-a-chip systems. There is great demand for manufacturing techniques capable of fabricating ever more intricate microstructures for increasingly complex applications whilst remaining cost-effective for use in biomedical research. Conventional manufacturing techniques can be used to fabricate many complex microchannel architectures but are often expensive, low throughput, have poor microfeature resolution or are unsuitable to be used at scale. To address this issue, we describe a manufacturing technique that employs stereolithography 3D printing to produce a base substrate which can be sealed with a laser patterned adhesive layer cover and stacked in a compact configuration. The technique provides for the design and manufacturing of a device that can be massively parallelized at relatively low cost and with a small laboratory footprint. This paper aims to fully explain the design and manufacturing process undertaken to allow the use of this technique in future research.